Complementary effects on vibration characteristics of functionally graded graphene reinforced magnetorheological elastomer sandwich plates. (1st November 2022) - Zhao, Jing; Wang, Tianhao; Ma, Xiaoguang; Li, Hui; Hu, Jinzhai; Liu, Jincan; Gao, Zhijiang
Highlights: A novel sandwich plate is proposed with the complementary effects-based design method. The structural vibration attenuation capacity is strengthened by introducing the MRE core. The dynamic behaviors of the sandwich plate are revealed based on the Rayleigh-Ritz method. The magnetic-mechanical coupling model is constructed based on the energy method. Abstract: This study proposes a novel method to improve the vibration characteristics of sandwich plates based on the complementary effects of various materials. To investigate the complementary effects, a unified modeling method on the functionally graded graphene-reinforced layers magnetorheological elastomer (FGGR-MRE) sandwich plate is proposed, and the influence mechanism of internal and external factors on the complementary effect is clarified. Four novel material distributed profiles are proposed to define the nonlinear interaction between the MRE and FGGR layers, and a novel constitutive relationship of the proposed plate is established with the magnetic-mechanical coupling via the Maxwell's equation. Moreover, the dynamic characteristics of the FGGR-MRE sandwich plates are obtained by employing the modified Fourier series and the Rayleigh-Ritz method. Finally, the convergence and accuracy of the proposed model are verified under free and forced vibration conditions, and numerical investigations are carried to examine the complementary effects of the FGGR-MRE sandwich plate. The results show that the introduction of graphene platelets (GPLs) can greatly increase the resonance frequency of the sandwich plate, while the MRE can significantly accelerate the vibration attenuation of the structure. Compared with the traditional design method, the complementary effects-based design method can comprehensively improve the vibration characteristics of sandwich plates.